FEMININITY AS PORTRAYED IN QUENTIN JACOBSEN THE MAIN CHARACTER IN PAPER TOWNS NOVEL - Sari, Yuli Eka Purnia; Kuncara, Singgih Daru; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2018)
ABSTRACT Nowadays, gender issue is one of the issues that often discussed not only in literary works but also in our society. Actually, there are two terms of gender, those are masculinity and femininity. Those two terms are developed into gender stereotype which is structured by environment to differentiate between men and women. By this research, the researcher aimed to analyze the feminine traits of the male character, Quentin Jacobsen in Paper Towns novel and to analyze the supporting factor of Quentin?s feminine traits. This research was qualitative research which used content analysis as the data analysis technique. This research focused on Quentin?s femininity and its influencing factor that was found through the narrations and dialogues in the novel. To analyze Quentin?s femininity this research used Sandra L Bem Sex Role Inventory (BSRI) that was categorized by James L Park Gender-Pattern Chart. Then to reveal the influencing factors of Quentin?s feminine traits, this research used Correlated Factors of Gender Variance by Veale et.al. The result of this research showed that Quentin has nineteen feminine traits according to BSRI such as childlike, feminine, compassionate, sympathetic, shy, affectionate, cheerful, eager to soothe hurt feelings, flatter able, loves children, loyal, sensitive to needs of others, soft spoken, tender, understanding, warm, gentle, gullible, and yielding. Those traits were influenced by parental and abuse factor. Keywords: gender stereotype, femininity, masculinity, influencing factors  ABSTRAK Saat ini, isu tentang gender adalah salah satu isu yang sering dibahas tidak hanya pada karya sastra tetapi juga pada lingkungan sosial kita. Sebenarnya ada dua istilah dalam gender yaitu maskulin dan feminin. Kedua istilah tersebut kemudian menjadi stereotip yang terbentuk dari lingkungan untuk membedakan antara pria dan wanita. Dengan penelitian ini, peneliti bermaksud untuk menganalisa sifat feminin pada karakter laki-laki, Quentin Jacobsen di Paper Towns novel dan untuk menganalisa faktor yang mempengaruhi sifat feminin Quentin. Penelitian ini adalah penelitian kualitatif yang menggunakan konten analisis sebagai teknik analisis data. Penelitian ini fokus pada sifat feminin Quentin dan faktor yang mempengaruhinya yang ditemukan pada narasi dan dialog novel. Untuk menganalisis sifat feminin Quentin, penelitian ini menggunakan teori dari Sandra L Bem, Sex Role Inventory yang dikategorikan lagi berdasarkan Gender-Patter Chart oleh James L Park. Kemudian untuk mengungkap faktor yang mempengaruhi sifat feminin Quentin, penelitian ini menggunakan teori dari Veale dan kawan-kawan yaitu Correlated Factors of Gender Variance. Hasil yang didapat dari penelitian menunjukkan bahwa Quentin memiliki sembilan belas sifat feminin berdasarkan BSRI yaitu kekanak-kanakan, feminin, mudah merasa kasihan, simpatik, pemalu, penuh kasih sayang, periang, penenang, mudah dirayu, penyayang anak-anak, setia, peka, santun, berhati lembut, pengertian, hangat, lemah lembut, mudah dibohongi dan penurut. Sifat-sifat tersebut dipengaruhi oleh faktor orang tua dan faktor kekerasan.  Kata kunci: stereotip gender, feminin, maskulin, faktor yang mempengaruhi